A new maneuver for classical laryngeal mask airway insertion: Prospective randomized study: A new maneuver for cLMA insertion - Esen, Asım; Bakan, Mefkur; Topuz, Ufuk; Dursun, Zeynep Ertaş; Karaaslan, Kazım (Journal of Surgery and Medicine, 2022)
Background/Aim: Laryngeal mask airway (LMA) has been frequently used for airway management. But the satisfaction of the insertion and trauma at insertion remain problems. We present a new insertion maneuver for classical LMA (cLMA) with a partially inflated cuff and examine its success and complication rate. Methods: In 4 months, 158 patients who were classified as ASA I–III and older than 18 years old and were planned for LMA were included in this study consecutively (according to the study design, one patient was excluded during the study). Emergency cases, patients with any contraindications with LMA, patients who were expected to undergo surgery for more than 2 h, patients with preoperative respiratory tract infection or sore throat, patients undergoing oral or nasal surgery, and patients with aspirated oropharyngeal secretions after removal of LMA was excluded from the study. Age, gender, height, weight, ASA scores, comorbidities, and the duration of anesthesia and surgery of the patients were recorded. One-hundred-fifty-seven consecutive patients were randomized into two groups by a coin toss [control group (group C) and study group (group S)]. The groups were compared in terms of LMA insertion success, the number of insertion attempts, the presence of blood on the LMA or in secretions, and postoperative sore throat. Classical Laryngeal Mask Airway was inserted with Brain’s standard technique in group C and with the new technique in group S. In the new technique, the head and neck of the patient were supported in a straight position, the mouth was opened, cLMA was held with a dominant hand from the tube part and inserted until the tip touches to the oropharynx. The index finger of the non-dominant hand was inserted into the mouth to pass by the cLMA and reach the tip of the cLMA. The tip of cLMA was directed to the caudal by the index finger. Then, cLMA was inserted by the guidance of the index finger until it reached the triangular base of the oropharynx. Results: There was no statistically significant difference in terms of demographic data and placement success; placement success was better in the study group (100% versus 98.6% and P = 0.45). Similarly, the count of attempts was better in the study group. The mean attempt number was 1.11 in group S and 1.28 in group C (P = 0.02). Also, blood on LMA was seen to be more common in group C (P = 0.04). There were no statistical differences in sore throat, but it was less seen in group S. Conclusion: The new maneuver was better than the standard technique and easy to use in daily practice.